Strategi Komunikasi Kegiatan Corporate Citizenship Pt Krakatau Posco Dalam Membangun Kesadaran Stakeholder Sekunder - Aini, Sheva Nada; Christin, Maylanny (eProceedings of Management, 2024)
As industrial operational risks increase which have an impact on the wider community socially, economically andenvironmentally, building awareness of secondary Stakeholders has become a necessity for companies. Goodawareness of the surrounding community will minimize the potential for conflict and resistance that could hamper thecontinuity of company operations. This research aims to analyze the communication strategies implemented by PTKrakatau Posco in Corporate Citizenship activities to build awareness of secondary Stakeholders, especially thesurrounding community. This research uses a descriptive qualitative method with a case study approach, analysis iscarried out based on the communication strategy stages according to Hafied Cangara, including determining thecommunicator, target audience, compiling the message, determining media channels, forming a work team, andconducting evaluations. The research results show that PT Krakatau Posco implements an effective communicationstrategy at every stage so that it is able to build awareness of the surrounding community regarding the company'scontribution and commitment to realizing inclusive and sustainable growth. This research provides theoretical andpractical implications for the development of Corporate Citizenship communication strategies in building secondaryStakeholder awareness in the future. Keywords-communication strategy, corporate citizenship, secondary stakeholders.